Rectosigmoid perforations in anorectal malformations with perineal fistulae: The case of contrasting outcomes - Alex Osei Assim; Robert Sagoe; Anwar Sadat Seidu; Michael Amoah (Elsevier, 2022)
Anorectal malformation (ARM) constitutes a wide range of developmental anomalies affecting the distal part of the colon and the urogenital tracts. Rectosigmoid perforation complicating ARM with a perineal fistula discharging meconium and air is extremely uncommon and rarely reported. Here, we report two cases of rectosigmoid perforations in ARM with rectoperineal fistulae who had contrasting outcomes. Two full term male neonates, both with birth weight 3.2kg, Case 1 and case 2, were diagnosed with ARM with rectoperineal fistulae following clinical evaluation on day 2 and 4 of life respectively. There was no clinical suspicion of colonic perforation. Intraoperatively, however, a 5 × 2cm perforation was found extending from the distal colon to the proximal rectum for Case 1 whiles Case 2 had a 7 × 2.5cm rectosigmoid perforation. Both perforations were repaired primarily in single layer and a proximal divided sigmoid colostomy was mounted. Case 1 had an uneventful postoperative recovery and was discharged whereas Case 2 unfortunately died on post-operative day 2. Rectosigmoid perforation complicating ARM with rectoperineal fistula is rare, may be occult and carries significant threat to life. Early presentation, high index of suspicion and prompt surgical intervention are key to a good outcome.